Folliculotropic mycosis fungoides driven by DOCK8 immunodeficiency syndrome. Issue 1 (25th October 2020) - Rubio‐Gonzalez, Belen; Frieden, Ilona J.; McCalmont, Timothy H.; Dorsey, Morna; Funk, Tracy; Pincus, Laura B.
Abstract: DOCK8 immunodeficiency syndrome (DIDS) represents a rare primary immunodeficiency associated with cutaneous viral infections, allergy, and increased risk of malignancy. We report a case of folliculotropic mycosis fungoides with spontaneous resolution occurring in a patient with DIDS.